2018
DOI: 10.4038/jnsfsr.v46i4.8626
|View full text |Cite
|
Sign up to set email alerts
|

A new statistical distribution: cubic rank transmuted Kumaraswamy distribution and its properties

Abstract: This article suggests a new statistical distribution using cubic rank transmutation map. Various statistical estimators of unknown parameters of this distribution are derived. A Monte Carlo simulation study based on bias and mean square error criteria of this estimator is conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…In the real data analysis, the dataset from Dasgupta R [21] was considered first and from Table 3 shows that the CRTIW distribution has the best fit because it possesses the smallest AIC, BIC, AICc and -2loglikelihood among all fitted models and the same is also applicable for the data set of Cordeiro and Don Santos Brito [1], Brito RS. [22] and Bugra et al [18], has presented in Table 6. Based on our findings, CRTIW distribution can be used to model the two data sets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the real data analysis, the dataset from Dasgupta R [21] was considered first and from Table 3 shows that the CRTIW distribution has the best fit because it possesses the smallest AIC, BIC, AICc and -2loglikelihood among all fitted models and the same is also applicable for the data set of Cordeiro and Don Santos Brito [1], Brito RS. [22] and Bugra et al [18], has presented in Table 6. Based on our findings, CRTIW distribution can be used to model the two data sets.…”
Section: Resultsmentioning
confidence: 99%
“…Granzotto et al [9] have suggested cubic rank transmuted Weibull, cubic rank transmuted loglogistic distributions etc. Bugra Saracoglu et al [18], studied the properties of cubic rank transmuted kumaraswamy distribution, Cubic transmuted Gompertz distribution was studied by Ogunde AA et al [19] etc.…”
Section: Cubic Rank Transmuted Kumaraswamy (Crtiw) Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lists of several cubic transmuted distributions introduced by various researchers are mentioned in Table 2. Granzotto et al, [2] AL-Kadim and Mohammed [97] Rahman et al, [5] Rahman et al, [99] Ansari and Eledum [100] Rahman et al, [95] Celik [101] Celik [101] Celik [101] Saraҫoğlu and Tanɩş [102] Riffi and Hamdan [103] Ansari et al, [104] Rahman et al, [105] Bhatti et al, [106] Rahman et al, [96] Adeyinka [107] Cubic Transmuted Weibull…”
Section: Cubic Rank Transmutation Mapmentioning
confidence: 99%
“…Other commonly used distributions to modeled big survival data with extreme observations are Weibull, gamma, Gompertz, log-normal, loglogistic, generalized gamma, and generalized F-distribution. Also, the FPM can efficiently incorporate covariates to investigate the dependence of survival response in the context of estimated parameters, survival function, and cumulative hazard function [6][7][8][9][10]. Multivariate regression models assume that there is no multicollinearity among covariates of survival systems.…”
Section: Introductionmentioning
confidence: 99%